2022
DOI: 10.1007/s11356-022-22434-w
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide promotes V-Cu-Ce-ZSM-5 to catalyze SO2 and NO at low temperature: performance and mechanism

Abstract: A catalyst (V-Cu-Ce-ZSM-5) was explored to simultaneously remove the SO 2 and NOx from ue gas by use of the ZSM-5 molecular sieve as the carrier, V and Cu as the active components, and Ce as the additive in low temperature of 150℃. The performance of V-Cu-Ce-ZSM-5 was evaluated for the oxidation of NO and SO 2 before and after the addition of graphene oxide (GO). The results showed that V-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The catalyst was prepared by the sol gel method; catalyst particle size was controlled within the range of 30–50 mesh, and the specific steps are detailed in the Supporting Information. Numerous studies have demonstrated the significant activity and catalytic performance of copper and cerium in desulfurization reactions. Additionally, the different oxidation states and oxygen vacancy contents of copper and cerium may be the main factors leading to variations in their catalytic activity. , In desulfurization reactions, the different valence states of metallic elements can significantly affect the electronic structure and the reaction activity of the catalyst. It is possible to control the active sites and adsorption capacity on the catalyst surface, thereby optimizing the desulfurization reaction by adjusting the redox state of the metal elements. , Moreover, the oxygen vacancy content is also an important parameter in the desulfurization reactions.…”
Section: Experimental Setup and Activity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst was prepared by the sol gel method; catalyst particle size was controlled within the range of 30–50 mesh, and the specific steps are detailed in the Supporting Information. Numerous studies have demonstrated the significant activity and catalytic performance of copper and cerium in desulfurization reactions. Additionally, the different oxidation states and oxygen vacancy contents of copper and cerium may be the main factors leading to variations in their catalytic activity. , In desulfurization reactions, the different valence states of metallic elements can significantly affect the electronic structure and the reaction activity of the catalyst. It is possible to control the active sites and adsorption capacity on the catalyst surface, thereby optimizing the desulfurization reaction by adjusting the redox state of the metal elements. , Moreover, the oxygen vacancy content is also an important parameter in the desulfurization reactions.…”
Section: Experimental Setup and Activity Measurementsmentioning
confidence: 99%
“…13−15 Additionally, the different oxidation states and oxygen vacancy contents of copper and cerium may be the main factors leading to variations in their catalytic activity. 13,14 In desulfurization reactions, the different valence states of metallic elements can significantly affect the electronic structure and the reaction activity of the catalyst. It is possible to control the active sites and adsorption capacity on the catalyst surface, thereby optimizing the desulfurization reaction by adjusting the redox state of the metal elements.…”
mentioning
confidence: 99%